2011
DOI: 10.1111/j.1537-2995.2010.02795.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Jk(a+weak): a new blood group phenotype associated with an altered JK*01 allele

Abstract: A new phenotype with weakened Jk(a) expression on RBCs is associated with a JK*01-like allele, which may constitute a risk for hemolytic transfusion reactions if antigen-positive units are missed by routine serology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 30 publications
1
27
0
Order By: Relevance
“…These observations show that HIRO-294 is able to recognise the Jk a /Jk b polymorphic site located on the fourth extracellular loop of the Kidd glycoprotein. It has been described that the c.130G>A (p.Glu44Lys) mutation detected in the JK*01W.01 allele reduced the expression of the Kidd glycoprotein, corresponding to the Jk(a+ w ) phenotype (Wester et al, 2011). We also confirmed the weak reactivity of c.130A/A RBCs with HIRO-294 by flow cytometry.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…These observations show that HIRO-294 is able to recognise the Jk a /Jk b polymorphic site located on the fourth extracellular loop of the Kidd glycoprotein. It has been described that the c.130G>A (p.Glu44Lys) mutation detected in the JK*01W.01 allele reduced the expression of the Kidd glycoprotein, corresponding to the Jk(a+ w ) phenotype (Wester et al, 2011). We also confirmed the weak reactivity of c.130A/A RBCs with HIRO-294 by flow cytometry.…”
Section: Discussionsupporting
confidence: 80%
“…During the hemagglutination titration study, we noticed that the reactivity of HIRO‐294 with the Jk(a+b−) cells was weaker than that of the Jk(a−b+) cells (Table ). A previous report indicated that the JK*01W.01 allele having the c.130G>A (p.Glu44Lys) mutation affected the expression of Kidd glycoprotein, accounting for the Jk(a+ w ) phenotype, and the allele was relatively common in Asian people (Wester et al, ). Therefore, we investigated the relationship between the c.130 genotype determined by multiplex PCR (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many discrepancies were associated with samples with single‐dose Fy b expression that were not originally detected as positive; 86% of Fy b discrepancies reacted weak+ to 2 + on the repeat serologic testing (http://onlinelibrary.wiley.com/doi/10.1111/trf.12987/suppinfo). Direct sequencing revealed one Jk a discrepancy explained by a JK*A nucleotide 130G>A change associated with weak antigen expression. Overall, discrepant results were equally associated with false‐positive (n = 34) and false‐negative (n = 33) historical serologic types.…”
Section: Resultsmentioning
confidence: 98%
“…The molecular basis for the two main JK antigens is located at Nucleotide 838 (G for Jk a (Asp280), A for Jk b (Asn280)). Null alleles have been described in all populations, but are more frequent in Polynesian and Finn persons, and variant alleles are also described in black persons …”
Section: Background and Case Reportmentioning
confidence: 99%